THE ARTEMIS ACCORDS AND PROPERTY RIGHTS IN OUTER SPACE - Regi Rivaldi (Journal of Law and Policy Transformation, 2022)
On 13 October 2020, The National Aeronautics and Space Administration (NASA) and the representatives of eight other space-faring nations signed The Artemis Accords. The Accords is a set of 13 provisions to establish international collaboration on sustainable human exploration in outer space. The most controversial provision in the Accords is the provision in Section 10 that relates to exploiting space resources which is not inherent with Article II of The Outer Space Treaty and Article 11 of The Moon Agreement that will cause the implementation of the Artemis Accords may violate international law. The different interpretations in interpreting the provisions in Article II of The Outer Space Treaty raises questions related to property rights in outer space, especially on issues that are related to the extraction of natural resources. Is it part of the subject of the non-appropriation principle or not.